2020
DOI: 10.1002/rmv.2165
|View full text |Cite
|
Sign up to set email alerts
|

HIV‐1 viral load testing in resource‐limited settings: Challenges and solutions for specimen integrity

Abstract: Summary HIV‐1 viral load (VL) testing is a crucial element in providing an antiretroviral treatment monitoring program. The success of these programs depends on the availability and quality of the VL testing services. There are several pre‐analytic factors which can affect the quality of VL testing. Many of the challenges faced by resource‐limited countries result in a compromise of specimen integrity, thus limiting widespread access to VL monitoring. The various logistic and financial challenges that exist ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 34 publications
(117 reference statements)
0
9
1
Order By: Relevance
“…The possible application of this finding depends on the ongoing roll out of viral load monitoring in line with the WHO guidelines and is still limited in these settings. 17 The analyses also showed that a longer duration of HIV infection was associated with both a higher risk of TB (Table 2) and other non-TB AIDS events. Despite ART treatment, the duration of HIV infection should be considered in the clinical management of this population who continue to experience a greater risk of AIDS-related morbidity.…”
Section: Discussionmentioning
confidence: 87%
“…The possible application of this finding depends on the ongoing roll out of viral load monitoring in line with the WHO guidelines and is still limited in these settings. 17 The analyses also showed that a longer duration of HIV infection was associated with both a higher risk of TB (Table 2) and other non-TB AIDS events. Despite ART treatment, the duration of HIV infection should be considered in the clinical management of this population who continue to experience a greater risk of AIDS-related morbidity.…”
Section: Discussionmentioning
confidence: 87%
“… 12 The stability of PSC specimens stored at high temperatures for up to 28 days is an important feature for field conditions in resource-limited settings, given that in most sub-Saharan African countries, preshipment storage at health facilities and transportation of specimens to the reference laboratories can take up to a month. 16 …”
Section: Discussionmentioning
confidence: 99%
“…10,32 As in other countries in sub-Saharan Africa, fidelity to the recommended VL testing schedules was challenging in Nigeria, resulting in missed measures. [33][34][35] VL testing was completed at reference laboratories after whole blood sample collection at the facilities using Roche COBAS AmpliPrep/ TaqMan HIV-1 Test. For the primary analyses, which used only routine patient data, we included participants with .1 VL measure in the study period.…”
Section: Analysis Measures and Definition Of Variablesmentioning
confidence: 99%